Simulation of regional soil moisture deficits on a European scale - Cramer,W; Prentice,IC (Norsk Geografisk Tidsskrift, 1988)
A simple deterministic simulation model for landscape-scale soil water deficits has been developed. Standard weather station data are used to estimate ‘daily’ precipitation and actual (regional) evapo- ranspiration (AET). The balance is added to soil moisture, which is accounted by a simple bucket nodel. AET is the daily integral of the lesser of supply and demand: Supply is governed by current oil moisture, demand by estimated net radiation and temperature. The model estimates geographical atterns of soil water deficit at a scale suitable for comparison with the distributions of plant species md vegetation types. The model provides a way of quantifying soil moisture stress in biogeographical esearch. © 1988 Taylor & Francis Group, LLC.